Educação em saúde e repercussão nos fatores de risco para hipertensão arterial sistêmica no judiciário do Estado do Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
Systemic arterial hypertension is the most frequent of cardiovascular diseases and responds as the main risk factor for the most common complications such as: stroke and acute myocardial infarction, in addition to end-stage chronic kidney disease. Health education is an important tool to guide healthy habits and lifestyles, which are fundamental to the prevention of this pathology. The objective was to analyze the influence of educational health actions promoted within the scope of the Court of Justice of the State of Amapá, in changing the lifestyle of workers. This is a descriptive study, with a quantitative approach. A questionnaire was used as a data collection instrument, composed of 46 closed questions. 255 servers participated. The collected data were tabulated by double digitization, for comparison and validation of the bank. Data analysis was performed using the Statistical Package for Social Science SPSS version 22 for univariate and bivariate forms. In the descriptive analysis, frequency distribution was observed between sex and sociodemographic variables, physical and clinical data. In inferential analysis, Pearson's chi-square test (χ2) was used to analyze the association between arterial hypertension and sociodemographic variables, physical and clinical data, habits and lifestyle, chronic diseases and health status and health education. Α = 0.05 was used in all tests. The results showed that 54.1% were female, 66.3% were brown, 33.7% were between 40 and 49 years old, 47.8% had higher education and 59.6% were married and or lived in stable union. The Body Mass Index showed that 48.2% were overweight, 64.7% had increased waist circumference, 10.6% had capillary blood glucose values ≥ 99 mg / dL. As for blood pressure, 33.3% of men and 21.7% of women had BP ≥ 140 and / or 90 mmHg. Regarding participation in some preventive or educational activity, 76.1% said yes, 60.4% considered it satisfactory and 49% did not influence the change in lifestyle. It is proven that health education actions are partially impacting the change in workers' habits with a focus on reducing risk factors for systemic arterial hypertension, as the risk factor indexes are still a cause for concern.
Keywords: Hipertensão arterial sistêmica; Acidente vascular cerebral - Risco; Infarto agudo do miocárdio - Risco; Educação em saúde; CNPQ::CIENCIAS DA SAUDE